Chili Yields, Nutrient Use, and Water Use Efficiency under Precision Fertigation at Different Plant Density and Drip Irrigation Lines - Susila, Anas Dinurrohman; Suketi, Ketty; Purnamawati, Heni; Rusdan, Risna (Journal of Tropical Crop Science, 2025)
The study aimed to evaluate the effects of irrigation line number and plant density on the growth and yield of curly red chili pepper (Capsicum annuum L.) cv. Tangguh. The study was conducted from August 2023 to January 2024 at the Cikarawang Experimental Station of IPB University (6°32’56” S; 106°43’54” E; 240 m above sea level) on Ultisol characterized by severely low phosphorus (1.1 ppm) and high potassium content (66 ppm). A split-plot design within a randomized complete block design was employed, with irrigation line number (single or double drip lines per bed) as the main plot and four planting densities (26,666, 53,322, 80,000, and 106,666 plants.ha-1) as subplots. Each treatment was replicated three times, resulting in 24 plots (each 1.5 m × 10 m). Fertilizers applied included Urea (45% N), SP-36 (36% P2O5 ), cattle manure, dolomite, biofertilizers (Trichoderma spp.), and PGPR. Irrigation and fertigation were managed using the Nutrigads automatic drip system. The data collected included plant growth, yield components, nutrient use efficiency, water use efficiency, and partial factor productivity for nitrogen (N) and phosphorus (P). The results showed that the irrigation line number had no significant effect on individual plant growth parameters. However, using double lines significantly increased total fruit yield per bed and hectare, indicating its contribution to overall productivity. Conversely, the double line system reduced water use efficiency (WUE = 2.07 kg.mm-1) compared to the single line system (WUE = 3.64 kg.mm-1; P<0.0001). Higher planting densities (up to 106,666 plants.ha-1) enhanced total yield by promoting vertical growth but reduced individual plant performance, and had a positive effect on WUE, NUE, and PUE.